Effects of stocking-density in flow-through system on the mussel Perna perna larval survival - Caio Silva Turini; Simone Sühnel; Francisco José Lagreze-Squella; Jaime Fernando Ferreira; Claudio Manoel Rodrigues de Melo (Acta Scientiarum. Animal Sciences, 2014)
This study evaluated the effects of larval densities, cultured in flow-through system, in the yield and quantity of larvae. The first experiment compared the larval yield of a flowthrough system (80 larvae mL-1) and a batch system (8 larvae mL-1), which resulted in a higher yield and number of larvae in the flowthrough system, after 23 days. The second experiment compared two larval densities (20 and 45 larvae mL-1) in flowthrough system. The densities affected the yield after 15 and 23 days and the larvae final quantity after all tested times (8, 15, and 23 days). After 23 days of larviculture, the yield was highest for 20 larvae mL-1 and the larval number for 45 larvae mL-1. The third experiment also compared two larval densities (100 and 150 larvae mL-1) in flowthrough system. The larvae densities did not affect the yield and number of larvae for all tested times (8, 15, and 23 days). In general, the yield has reduced at higher larval densities. Therefore, considering the number of suitable larvae for settlement, the flow-through system was more efficient than the static system. However, in general, we observed reduced yield with high larval stocking-density in flow-through system.